Statistical multi-metric based eutrophication index: Case of study at Batam Marine Reserve Park - Hedi Indra Januar; Asri Pratitis; Rini Susilowati (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
Excessive human waste nutrients, which usually consist of nitrogenous and phosphate compounds, are known as the major environmental stresses in coastal waters. Therefore, monitoring of nutrients level is very important in marine reserve park. This study presents an application of multi-metric index in accessing the spatial and temporal level of a nutrient in surface water at Batam City Marine Reserve Park, Indonesia. Research had been done with seasonal and spatial zones on three major islands namely Petong, Abang, and Dedep. Water samples from each station were taken from the surface water. Phosphate, nitrate, nitrite, and ammonia, were analyzed in situ and chlorophyll was conducted in the laboratory by spectrophotometric method. Statistical multi-metric detected the average eutrophication index (EI) value between 0.2-0.7, which is mesotrophic to eutrophic. Petong and Abang zones were categorized as eutrophic, and Dadap was mesotrophic. Continuous nutrients contamination throughout seasonal may be derived from sedimentation and domestic run-off from human-populated islands in the middle and northern region. Therefore, ecosystem rehabilitation and mitigation of anthropogenic run-off are needed to optimise the conservation management. Moreover, Dadap zone as the area with the least anthropogenic pressures is potential to be the core of conservation area in Batam City marine reserve park.